PENYATUAN HUKUM PAJAK FORMAL DALAM SISTEM HUKUM PAJAK NASIONAL - Iwan Suhardi (Universitas Airlangga, 2016)
Characteristic of a tax system can be seen in the formal tax law that governs the tax collection procedure. Old tax law, such as as the Indonesian colonial tax law system is complex and is difficult to manifest. To tackle this problem, consolidated formal tax law such as General Provisions and Procedures of Taxation (UU KUP) has been used since 1983 to simplify the national tax law system. Result of this study showed that in practice, Indonesian tax system is still too complex. There are three main reasons for the observed complexity: First, inconsistency of the lawmaker and the policy maker. Separation between formal tax law and material tax law only occurs in the early reformation of tax law. In the sequential tax law reformation, the formal and material tax laws are coalesced together, going backward to the time prior to the national tax law system reformation. Second, UU KUP has not been able to accommodate all tax systems that are used in Indonesia, including the official assessment system. Third, there are disharmonisation between UU KUP and other formal tax law such as tax court law (UU Pengadilan Pajak). One potential solution is to return UU KUP to its original state as in 1983. In addition, UU KUP must be used as the sole formal tax law for all tax and UU KUP must accommodate all tax law system.